Austroliberalismo en Ibn Jaldún - García, Carlos Villaescusa García (REVISTA PROCESOS DE MERCADO, 2011)
Ibn Khaldun’s contributions to the development of economic thought in his great work al-Muqaddima have received almost no attention in Western academia. This paper studies the similarities between the thought of Ibn Khaldun and that of the leading authors of the liberal Austrian School, including Ludwig von Mises and Friedrich August von Hayek, and The School of Salamanca. Special attention is given to Professor Jesús Huerta de Soto’s work on the theory of the impossibility of socialism. This paper also examines how statist coercion and interventionism in areas such as trade, taxation and individual rights promote injustice and will lead to the eventual demise of civilization. The work of Ibn Khaldun captured the essence of a spontaneous order and of the evolution of institutions, and refuted the theory of the divine origin of kings well before the Age of Enlightenment. Lastly, this paper touches on important economic issues of interest to Austrian liberals such as the division of labor and specialization, cooperation, the role of markets, the price system, savings as a rationale for prosperity, the relation of wealth to population, the Laffer curve, the quantity theory of money, the subjective nature of value, and the correct interpretation of history. Key words: Liberalism, interventionism, coercion, Salamanca School, Austrian School. JEL Classification: B53. Resumen: Las contribuciones de Ibn Jaldún al desarrollo del pensamiento económico incluidas en su gran obra al-Muqaddima han pasado casi desaper - cibidos en el ámbito académico occidental. En este trabajo se examinan las similitudes entre el pensamiento de Ibn Jaldún y el de los principales autores del austro-liberalismo, como Ludwig von Mises y Friedrich August von Hayek, y con el de la Escuela de Salamanca. Prestando especial atención a Jesús Huerta de Soto y su teoría de la imposibilidad del socialismo desde el punto de vista de la coacción: los efectos negativos de la interferencia del Estado en el co-mercio, los impuestos y contra los derechos individuales que derivan en la in-justicia que causa la ruina de la civilización. Mostramos cómo Ibn Jaldún capta la esencia de un orden espontáneo y evolutivo de las instituciones, refuta la teoría del origen divino de los reyes anticipándose a la ilustración ya desde la Edad Media. Y en definitiva, aspectos económicos importantes comunes con las corrientes austro-liberales como son: la división del trabajo o especialización, la cooperación, el papel de los mercados, el sistema de precios, el ahorro como condición para la prosperidad, la riqueza de las naciones por razones de mayor o menor población, el concepto de la curva de Laffer, una intuición de la teoría cuantitativa del dinero, compresión de la naturaleza subjetiva del valor, o la interpretación correcta de la historia. Palabras clave: Liberalismo, intervencionismo, coacción, Escuela Salamanca, Escuela Austriaca. Clasificación JEL: B53.